The rhetorical story in corporate social responsibility disclosure PT semen Padang - Sany Dwita, Charoline Cheisviyanny, Herlina Helmy, Nayang Helmayunita, (Opción, 2019)
This study aims to see whether there is a rhetorical story in the disclosure of Corporate Social Responsibility (CSR) information of PT Semen Padang in annual report and sustainability report. Rhetorical analysis is done through content analysis to the annual report and sustainability report compared with online news and semi-structured interview to relevant parties. The results of this study indicate the existence of rhetoric, both positive and negative, in disclosure of CSR information. In conclusion, the sustainability of Semen Padang will be more secure if accompanied by blessings and a good reputation in the eyes of the community